2023
DOI: 10.1111/cdoe.12896
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries in the Myanmar population: Findings from the first national oral health survey in 2016–2017

Abstract: ObjectivesThis study aimed to investigate the dental caries status of indicator age groups as mentioned in the WHO pathfinder methodology, compare caries experiences among those age groups according to gender and geographical location, and assess the association between dental caries and related risk factors in primary and permanent dentition.MethodsA sample of 5928 participants aged 6, 12, 15–18, 35–44 and 60–74 years were recruited from 21 selected townships in the first Myanmar national oral health survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The results of this study provide the updated prevalence of ECC and associated factors among five-year-old children in Mandalay, Myanmar, which could be used to develop oral health prevention and promotion strategies for this age group. The results of this study showed similar caries and dmft prevalence rates to those reported in the Myanmar National Oral Health Survey (84.1% and 5.71) ( 20 , 21 ) and in other studies conducted in different cities including in Naypyidaw (81.3%, 4.26 ± 3.76) ( 22 ) and Yangon (84.1%, 5.84 ± 4.57) ( 19 ). These findings demonstrated that ECC prevalence remains high and severe among young Myanmar children.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The results of this study provide the updated prevalence of ECC and associated factors among five-year-old children in Mandalay, Myanmar, which could be used to develop oral health prevention and promotion strategies for this age group. The results of this study showed similar caries and dmft prevalence rates to those reported in the Myanmar National Oral Health Survey (84.1% and 5.71) ( 20 , 21 ) and in other studies conducted in different cities including in Naypyidaw (81.3%, 4.26 ± 3.76) ( 22 ) and Yangon (84.1%, 5.84 ± 4.57) ( 19 ). These findings demonstrated that ECC prevalence remains high and severe among young Myanmar children.…”
Section: Discussionsupporting
confidence: 88%
“…According to the systematic review conducted in Southeast Asia countries, children aged five to six years had a particularly high prevalence (25%-95%) of ECC (17). The Republic of the Union of Myanmar, a Southeast Asia country with a population of approximately 54 million people, is among the country where ECC is highly prevalent among young children (18)(19)(20)(21). According to the National Oral Health survey (2016-2017), the mean dmft of 6-year-old-school children was 5.7 whereas the prevalence of untreated caries was 84.1% (20,21).…”
mentioning
confidence: 99%
See 3 more Smart Citations